2019
DOI: 10.1111/aji.13188
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐7, T helper 1, and regulatory T‐cell activity‐related cytokines are increased during the second trimester of healthy pregnancy compared to non‐pregnant women

Abstract: ProblemHealthy pregnancy is associated with a physiologic increase in inflammatory responses. The objective of this study was to assess changes in plasma cytokines associated with uncomplicated pregnancy.Method of studyTo examine these changes, plasma levels of immune response mediators from healthy gravidas (N = 115, gestation weeks 23‐30) were compared with those from healthy non‐pregnant women (N = 42). Comparisons were performed using multiplex analysis for Th1 activity‐related cytokines (IFN‐γ, IL‐2, sIL‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…A role for CRP in this context supports the anti-inflammatory state of second trimester ( 1 , 10 ) and warrants caution for using CRP alone to monitor inflammation in pregnancy. IL-7 also peaked in the second trimester and has been suggested important for maintaining fetal tolerance through the induction of δγ T cells and uterine NK cells ( 61 ). Previously, increasing ( 4 ) or stable ( 15 , 62 ) levels of IL-7 have been reported, but then measured at different time points in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…A role for CRP in this context supports the anti-inflammatory state of second trimester ( 1 , 10 ) and warrants caution for using CRP alone to monitor inflammation in pregnancy. IL-7 also peaked in the second trimester and has been suggested important for maintaining fetal tolerance through the induction of δγ T cells and uterine NK cells ( 61 ). Previously, increasing ( 4 ) or stable ( 15 , 62 ) levels of IL-7 have been reported, but then measured at different time points in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies investigating serum cytokine levels in healthy pregnancy over the three trimesters have been inconsistent. A recent study showed increased levels of both Treg cytokines (IL-10, sTNFRII) as well as Th1 cytokines (INFg, IL-2, IL-12, IL-27) during the second trimester of pregnancy [51]. Two studies reported a decrease in TNFa from early to late pregnancy [52,53], although three other studies did not corroborate this finding [54e56] and one reported an increase of TNFa across the trimesters [57].…”
Section: Immunology Of Pregnancy Outside the Uterusmentioning
confidence: 99%
“…These findings were in line with our study, as IL-27/IL-27 R expression was detected in peripheral blood, chorion, decidua, myometrium, and placenta of normal pregnancies (Figure 1). Depending upon the conditions, the IL-27/IL-27R exerts either pro-inflammatory or antiinflammatory effects to maintain the immune homeostasis in pregnancy [50][51][52]. Thus, altered levels of IL-27/IL-27R are of great importance in the development of gestational complications.…”
Section: Discussionmentioning
confidence: 99%